Macrolides in critically ill patients with Middle East Respiratory Syndrome. (April 2019) - Arabi, Yaseen M.; Deeb, Ahmad M.; Al-Hameed, Fahad; Mandourah, Yasser; Almekhlafi, Ghaleb A.; Sindi, Anees A.; Al-Omari, Awad; Shalhoub, Sarah; Mady, Ahmed; Alraddadi, Basem; Almotairi, Abdullah; Al Khatib, Kasim; et al.
Highlights: More than one-third of critically ill patients with Middle East Respiratory Syndrome Coronavirus (MERS-CoV) received empiric therapy with macrolides. Macrolide therapy is not significantly associated with a reduction in 90-day mortality of critically ill patients with MERS-CoV. Macrolide therapy is not significantly associated with improvement in MERS-CoV RNA clearance of critically ill patients with MERS-CoV. Abstract: Objectives: Macrolides have been reported to be associated with improved outcomes in patients with viral pneumonia related to influenza and other viruses, possibly because of their immune-modulatory effects. Macrolides have frequently been used in patients with Middle East Respiratory Syndrome (MERS). This study investigated the association of macrolides with 90-day mortality and MERS coronavirus (CoV) RNA clearance in critically ill patients with MERS. Methods: This retrospective analysis of a multicenter cohort database included 14 tertiary-care hospitals in five cities in Saudi Arabia. Multivariate logistic-regression analysis was used to determine the association of macrolide therapy with 90-day mortality, and the Cox-proportional hazard model to determine the association of macrolide therapy with MERS-CoV RNA clearance. Results: Of 349 critically ill MERS patients, 136 (39%) received macrolide therapy. Azithromycin was most commonly used (97/136; 71.3%). Macrolide therapy was commonly started before the patient arrived in the intensive care unit (ICU) (51/136; 37.5%), or on day1 in ICU (53/136; 39%). On admission to ICU, the baseline characteristics of patients who received and did not receive macrolides were similar, including demographic data and sequential organ failure assessment score. However, patients who received macrolides were more likely to be admitted with community-acquired MERS ( P  = 0.02). Macrolide therapy was not independently associated with a significant difference in 90-day mortality (adjusted odds ratio [OR]: 0.84; 95% confidence interval [CI] :0.47–1.51; P  = 0.56) or MERS-CoV RNA clearance (adjusted HR: 0.88; 95% CI:0.47–1.64; P  = 0.68). Conclusions: These findings indicate that macrolide therapy is not associated with a reduction in 90-day mortality or improvement in MERS-CoV RNA clearance.